Nonaqueous electrolyte and nonaqueous electrolyte secondary battery comprising said nonaqueous electrolyte
By using an electrolyte system containing ester compounds with specific carbon-carbon unsaturated bonds and specific electrolyte salts in a nonaqueous electrolyte secondary battery, the problem of increasing DC resistance of the battery after high temperature storage is solved, and the battery performance and life are significantly improved.
Patent Information
- Application Number
- JP2021034904
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-03-05
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2041-03-05
AI Technical Summary
The problem of increasing direct current resistance (DCR) of existing nonaqueous electrolyte secondary batteries after high temperature storage affects battery performance.
The non-aqueous electrolyte battery is added to the non-aqueous electrolyte battery with ester compounds containing specific carbon-carbon unsaturated bonds and electrolyte salts such as phosphates, sulfates or borates to form a new electrolyte system.
It effectively suppresses the increase in DC resistance of nonaqueous electrolyte secondary batteries after high temperature storage, and improves the performance and life of the battery.
Smart Images

Figure 0007660397000001 
Figure 0007660397000002 
Figure 0007660397000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a nonaqueous electrolyte solution and a nonaqueous electrolyte secondary battery comprising the nonaqueous electrolyte solution. [Background technology]
[0002] Lithium nonaqueous electrolyte secondary batteries, which use a lithium-containing transition metal oxide as a positive electrode and a nonaqueous solvent as an electrolyte, can achieve high energy density and are therefore used in a wide range of applications, from small power sources for mobile phones and laptop computers to large power sources for automobiles, railways, and load leveling. However, in recent years, there has been an increasing demand for higher performance for nonaqueous electrolyte secondary batteries, and there is a strong demand for improvements in various characteristics.
[0003] Up to now, methods have been proposed for improving the battery characteristics of energy devices by adding a specific additive to the electrolyte or by combining a specific electrolyte with an electrode. For example, Patent Document 1 relates to an electrolyte for an electricity storage device, particularly for a lithium ion storage battery containing a Si-based negative electrode active material, and proposes improving the discharge capacity retention rate during cycling of the electricity storage device by providing a negative electrode containing a Si-based negative electrode active material and a non-aqueous electrolyte containing an ester compound having a specific carbon-carbon double bond.
[0004] Patent Document 2 proposes an electrolyte solution containing a specific saturated chain carboxylate and an unsaturated chain carboxylate in order to improve the discharge capacity retention rate during charge-discharge cycles of a nonaqueous electrolyte battery.
[0005] Patent Document 3 proposes that a specific unsaturated carboxylic acid ester is contained in the electrolyte and housed in a specific exterior member to form a nonaqueous electrolyte secondary battery in order to suppress expansion of the battery during high-temperature storage while improving the discharge capacity retention rate during cycling.
[0006] Patent Document 4 proposes a non-aqueous electrolyte solution containing a specific polymerizable organic compound in order to improve high-temperature characteristics and storage characteristics of a lithium secondary battery that uses spinel-type lithium manganese oxide as a positive electrode active material. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] International Publication No. 2019-113528 [Patent Document 2] JP 2007-335170 A [Patent Document 3] JP 2009-152133 A [Patent Document 4] JP 2000-223154 A Summary of the Invention [Problem to be solved by the invention]
[0008] In recent years, non-aqueous electrolyte secondary batteries have increasingly required higher characteristics, particularly for battery-equipped automobiles, and there is a high demand for improved battery capacity after high-temperature storage. To date, for example, phosphates such as lithium difluorophosphate have been studied as additives for non-aqueous electrolyte secondary batteries. However, Patent Document 1 considers the improvement of the capacity retention rate during cycling of a non-aqueous electrolyte secondary battery by combining a negative electrode containing a specific negative electrode active material and a non-aqueous electrolyte containing an ester compound having a carbon-carbon double bond, but does not pay attention to or consider the battery resistance after high-temperature storage. Also, Patent Document 2 considers the improvement of the discharge capacity retention rate during cycle testing, but does not pay attention to the battery resistance after high-temperature storage. It has not been studied. Furthermore, Patent Document 3 considers the improvement of cycle characteristics by combining a specific exterior member with an electrolyte solution having a specific unsaturated carboxylate ester, but only describes that the electrolyte solution contains a solvent and an electrolyte salt dissolved in the solvent as components other than the specific unsaturated carboxylate ester, and that it is preferable to contain a halogenated carbonate ester or a carbonate ester having a carbon-carbon multiple bond. Furthermore, Patent Document 4 considers the improvement of the discharge capacity retention rate in the charge-discharge cycle by selecting an additive suitable for the saturated chain carboxylate ester, but only describes that the nonaqueous electrolyte solution contains a solvent and an electrolyte salt dissolved in the solvent as components other than the specific saturated and unsaturated chain carboxylate ester.
[0009] An object of the present invention is to provide a non-aqueous electrolyte that can suppress an increase in direct current resistance (DCR) of a non-aqueous electrolyte secondary battery after high-temperature storage. [Means for solving the problem]
[0010] As a result of intensive research aimed at solving the above-mentioned problems, the present inventors have found that the above-mentioned problems can be solved by causing a non-aqueous electrolyte solution to contain an ester compound having a specific carbon-carbon unsaturated bond, and a specific phosphate, sulfonate, or borate, and have arrived at the present invention.
[0011] That is, the gist of the present invention lies in the following. [1] A non-aqueous electrolyte solution comprising a compound (A) represented by formula (I) and one or more compounds (B) selected from the group consisting of phosphates having a PF bond and a P=O bond, sulfonates having an SF bond, and borates having a BF bond and / or an oxalate group. [ka] (In formula (I), R 1 ~R 6 are each independently a hydrogen atom, a halogen atom, or a hydrocarbon group; R1 and R 2 , R 1 and R 3 , R 4 and R 5 , and R 5 and R 6 may be bonded to each other to form a cyclic structure, and n is an integer of 0 to 4. [2] In the formula (I), R 1 ~R 6 are each independently a hydrogen atom, a halogen atom, an alkyl group having 1 to 6 carbon atoms, an alkenyl group having 2 to 6 carbon atoms, an aryl group having 6 to 12 carbon atoms, or an aralkyl group having 7 to 18 carbon atoms. [3] The nonaqueous electrolyte solution according to [1] or [2], wherein the compound (A) represented by the formula (I) is a vinyl ester compound represented by the following formula (II) and / or an allyl ester compound represented by the following formula (III): [ka] (In formula (II), R 7 ~R 9 are each independently a hydrogen atom, a halogen atom, or a hydrocarbon group; R 7 and R 8 , R 7 and R 9 may be bonded to each other to form a cyclic structure. [ka] (In formula (III), R 10 ~R 12 are each independently a hydrogen atom, a halogen atom, or a hydrocarbon group; R 10 and R 11 , R 10 and R 12 may be bonded to each other to form a cyclic structure. [4] The nonaqueous electrolyte solution according to any one of [1] to [3], wherein the compound (A) represented by the formula (I) is allyl methacrylate. [5] The nonaqueous electrolyte solution according to any one of [1] to [4], containing 0.01 mass % or more and 10 mass % or less of the compound (A) represented by the formula (I). [6] The nonaqueous electrolyte solution according to any one of [1] to [5], comprising 0.01 mass % or more and 10 mass % or less of one or more compounds (B) selected from the group consisting of phosphates having a PF bond and a P═O bond, sulfonates having an SF bond, borates having a BF bond, and borates having an oxalate group. [7] A nonaqueous electrolyte secondary battery comprising: a positive electrode having a positive electrode active material capable of absorbing and releasing metal ions; a negative electrode having a negative electrode active material capable of absorbing and releasing metal ions; and the nonaqueous electrolyte solution according to any one of [1] to [6]. Effect of the Invention
[0012] According to the present invention, it is possible to provide a nonaqueous electrolyte that can suppress an increase in the DCR of a nonaqueous electrolyte secondary battery after high-temperature storage, and also to provide a nonaqueous electrolyte secondary battery including the nonaqueous electrolyte. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] The following describes in detail the embodiment of the present invention. However, the following description is an example (representative example) of the embodiment of the present invention, and the present invention is not limited to these contents. In addition, the present invention can be modified and implemented as desired without departing from the gist of the present invention.
[0014] [1.Non-aqueous electrolyte] The nonaqueous electrolyte used in the nonaqueous electrolyte secondary battery according to the embodiment of the present invention, like a general nonaqueous electrolyte, contains an electrolyte and a nonaqueous solvent that dissolves the electrolyte, and further contains a compound (A) represented by formula (I) (hereinafter may be referred to as an ester compound having a carbon-carbon unsaturated bond) and one or more compounds (B) (hereinafter may be referred to as a "concomitant additive") selected from the group consisting of a phosphate having a PF bond and a P=O bond, a sulfonate having an SF bond, and a borate having a BF bond and / or an oxalate group. [ka] (In formula (I), R 1 ~R 6 are each independently a hydrogen atom, a halogen atom, or a hydrocarbon group; R 1 and R 3 , or R 4 and R 5 may be bonded to each other to form a cyclic structure, and n is an integer of 0 to 4. The non-aqueous electrolyte according to the present invention can improve the battery capacity after high-temperature storage. The inventors speculate that the reason for this effect is as follows. It is believed that as the secondary battery is charged and discharged, the carbon-carbon unsaturated bond of compound (A) represented by formula (I) reacts on the electrode to polymerize compound (A), which then reacts with one or more compounds (B) selected from the group consisting of phosphates having a PF bond and a P=O bond, sulfonates having an SF bond, and borates having a BF bond and / or an oxalate group, to form a hardly soluble and strong co-coating film on the electrode, thereby suppressing side reactions between the electrode active material and the solvent, etc. That is, it is believed that the present invention makes it possible to suppress the increase in DCR after high-temperature storage to a higher level than before by incorporating, in a nonaqueous electrolyte solution, an ester compound having a carbon-carbon unsaturated bond, and one or more compounds selected from the group consisting of a phosphate having a PF bond and a P=O bond, a sulfonate having an SF bond, and a borate having a BF bond and / or an oxalate group. Each component will be described below.
[0015] [1-1. Compound (A) represented by formula (I) (ester compound having a carbon-carbon unsaturated bond)] [ka]
[0016] In formula (I), R 1 ~R 6are each independently a hydrogen atom, a halogen atom, or a hydrocarbon group. Examples of the halogen atom include a fluorine atom, a chlorine atom, a bromine atom, and an iodine atom. Among these, a fluorine atom is preferred in terms of stability in the electrolyte. Examples of the hydrocarbon group include an alkyl group, an alkenyl group, an alkynyl group, an aryl group, and an aralkyl group. Among them, an alkyl group, an alkenyl group, an aryl group, and an aralkyl group are preferred, an alkyl group and an alkenyl group are more preferred, and an alkyl group is particularly preferred. The hydrocarbon group may have a substituent such as a fluorine atom. The aryl group also includes a heteroaryl group in which any ring atom is substituted with a heteroatom. Examples of the alkyl group include a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, a tert-butyl group, an n-pentyl group, a hexyl group, a heptyl group, an octyl group, a nonyl group, and a decyl group, etc. Among these, an alkyl group having 1 to 6 carbon atoms is preferable in terms of solubility in an electrolyte solution. Examples of the alkenyl group include a vinyl group, an allyl group, a methallyl group, a 2-butenyl group, a 3-methyl-2-butenyl group, a 3-butenyl group, a 4-pentenyl group, a 5-hexenyl group, a 6-heptenyl group, and a 7-octenyl group, etc. Among these, an alkenyl group having 2 to 6 carbon atoms is preferred in terms of solubility in an electrolyte solution. Examples of the alkynyl group include an ethynyl group, a 2-propynyl group, a 2-butynyl group, a 3-butynyl group, a 4-pentynyl group, a 5-hexynyl group, a 6-heptynyl group, and a 7-octynyl group. Among these, an alkynyl group having 2 to 6 carbon atoms is preferred in terms of solubility in an electrolyte solution. Examples of the aryl group include a phenyl group, a 1-naphthyl group, a 2-naphthyl group, a 2-thienyl group, a 3-thienyl group, a 2-furyl group, a 3-furyl group, a 2-pyrrolyl group, a 3-pyrrolyl group, and a benzyl group. Among these, an aryl group having 6 to 12 carbon atoms is preferred, and a phenyl group, a 1-naphthyl group, and a 2-naphthyl group are particularly preferred in terms of solubility in an electrolyte solution. Examples of the aralkyl group include a phenylmethyl group (benzyl group), a phenylethyl group (phenethyl group), a phenylpropyl group, a phenylbutyl group, and a phenylisopropyl group. Of these, benzyl and phenethyl groups are preferred, with the benzyl group being particularly preferred from the standpoint of stability in the electrolyte. R in formula (I) 1 and R 2 , R 1 and R 3 , R 4 and R 5 , or R 5 and R 6 may be bonded to each other to form a cyclic structure. 1 ~R 6 is R 1 and R 2 , R 1 and R 3 , R 4 and R 5 , or R 5 and R 6 In the ring formed by bonding together, a group generated when one CC bond is cleaved is also included. R 1 , R 2 And R 1 and R 2 or the carbon to which R 5 , R 6 And R 5 and R 6 Examples of the ring structure composed of carbon to which is bonded include alicyclic carbon rings such as a cyclohexene ring, a cyclopentene ring, etc. Among these, the cyclohexene ring is preferred in terms of stability in the electrolyte solution. R 1 , R 3 Also, R 1 and R 2 The carbon to which R is bonded 3 and a carbon-carbon double bond with the carbon to which the ester group is attached, R 4 , R 5 And R 4 and the carbon to which the oxygen atom of the methylene group or ester group is bonded and R 5 and R 6Examples of the cyclic structure composed of a carbon-carbon double bond with the carbon to which is bonded include alicyclic carbon rings such as cyclohexene ring and cyclopentene ring; aromatic rings such as benzene ring and naphthalene ring; and the like. Among them, cyclohexene ring, benzene ring, and naphthalene ring are preferred in terms of stability to the electrolyte, cyclohexene ring, benzene ring, and naphthalene ring are more preferred, and cyclohexene ring and benzene ring are even more preferred. In addition, the hydrogen atom of the cyclic structure may be substituted with a halogen atom such as a fluorine atom. R 1 ~R 6 is preferably a hydrogen atom or an alkyl group having 1 to 6 carbon atoms. n is an integer of 0 to 4, and is preferably an integer of 0 to 2, more preferably 0 or 1, and further preferably 1, in terms of solubility in the electrolyte.
[0017] From the viewpoint of stability in the electrolyte, a vinyl ester compound represented by the following general formula (II) and / or an allyl ester compound represented by the following general formula (III) are more preferable. [ka] (In formula (II), R 7 ~R 9 are each independently a hydrogen atom, a halogen atom, or a hydrocarbon group; R 7 and R 8 , R 7 and R 9 may be bonded to each other to form a cyclic structure. [ka] (In formula (III), R 10 ~R 12 are each independently a hydrogen atom, a halogen atom, or a hydrocarbon group; R 10 and R 11 , R 10 and R 12 may be bonded to each other to form a cyclic structure. R in general formula (II) 7 ~R9 and R in general formula (III) 10 ~R 12 are R in general formula (I), 1 ~R 3 is synonymous with.
[0018] Specific examples of the compound represented by formula (I) include the following compounds. [ka]
[0019] [ka]
[0020] Among these, the following compounds are preferred: [ka]
[0021] [ka]
[0022] More preferably, the following compounds are included: [ka]
[0023] [ka]
[0024] More preferably, the following compounds are included: [ka]
[0025] [ka]
[0026] More preferred examples of the compounds include the following: [ka]
[0027] More preferred are the following compounds, because excessive reactions on the electrodes can be suppressed. [ka]
[0028] The content of the compound represented by formula (I) is not particularly limited, but is usually 0.01 mass% or more, preferably 0.05 mass% or more, and usually 10 mass% or less, preferably 8 mass% or less, more preferably 6 mass% or less, and even more preferably 4 mass% or less, based on the total amount of the non-aqueous electrolyte. The compound represented by formula (I) may be used alone or in any combination and ratio of two or more. The identification and content of ester compounds having carbon-carbon unsaturated bonds are carried out by nuclear magnetic resonance (NMR) spectroscopy.
[0029] [1-2. Phosphates having PF bonds and P=O bonds, sulfonates having SF bonds, borates having BF bonds and / or oxalate groups: Compound (B) (co-added Agent)] [1-2-1. Phosphates with PF and P=O bonds] The phosphate salt having a PF bond and a P=O bond is not particularly limited, but specifically includes lithium monofluorophosphate, sodium monofluorophosphate, potassium monofluorophosphate, Examples of the phosphate salt include lithium monofluorophosphate, rubidium monofluorophosphate, cesium monofluorophosphate, lithium difluorophosphate, sodium difluorophosphate, potassium difluorophosphate, rubidium difluorophosphate, cesium difluorophosphate, lithium monofluoromonomethyl phosphate, sodium monofluoromonomethyl phosphate, potassium monofluoromonomethyl phosphate, rubidium monofluoromonomethyl phosphate, and cesium monofluoromonomethyl phosphate. Among these, lithium monofluorophosphate and lithium difluorophosphate are particularly preferred in terms of electrolyte stability. The content of the phosphate having a PF bond and a P=O bond is not particularly limited, but is usually 0.01 mass% or more, preferably 0.05 mass% or more, more preferably 0.1 mass% or more, and is usually 10 mass% or less, preferably 8 mass% or less, more preferably 6 mass% or less, based on the total amount of the nonaqueous electrolyte. The identification and content measurement of the phosphate having a PF bond and a P=O bond are performed by nuclear magnetic resonance (NMR) spectroscopy.
[0030] [1-2-2. Sulfonates having SF bonds] The sulfonate having an SF bond is not particularly limited, but specific examples thereof include fluorosulfonates such as lithium fluorosulfonate, sodium fluorosulfonate, potassium fluorosulfonate, rubidium fluorosulfonate, and cesium fluorosulfonate; fluorosulfonylimide salts such as lithium bisfluorosulfonylimide; etc. From the viewpoint of electrolyte stability, fluorosulfonates are preferred, and lithium fluorosulfonate is more preferred. The content of the sulfonate having an SF bond is not particularly limited, but is usually 0.01 mass% or more, preferably 0.05 mass% or more, more preferably 0.1 mass% or more, and is usually 10 mass% or less, preferably 8 mass% or less, more preferably 6 mass% or less, based on the total amount of the nonaqueous electrolysis.
[0031] [1-2-3. Borates having BF bonds and / or oxalate groups] The borate salt having a BF bond and / or an oxalate group of the present invention is not particularly limited, and specific examples thereof include borates having a BF bond such as lithium tetrafluoroborate, sodium tetrafluoroborate, potassium tetrafluoroborate, rubidium tetrafluoroborate, cesium tetrafluoroborate, lithium trifluoromonomethylborate, lithium difluorodimethylborate, and lithium trimethylmonofluoroborate; borates having an oxalate group such as lithium bisoxalate borate, sodium bisoxalate borate, potassium bisoxalate borate, rubidium bisoxalate borate, and cesium bisoxalate borate; and borates having a BF bond and an oxalate group such as lithium monooxalate difluoroborate, sodium monooxalate difluoroborate, potassium monooxalate difluoroborate, and cesium monooxalate difluoroborate. Among these, lithium tetrafluoroborate, sodium tetrafluoroborate, potassium tetrafluoroborate, lithium bisoxalatoborate, and lithium monooxalatodifluoroborate are particularly preferred in terms of electrolyte stability. The content of the borate having a BF bond and / or an oxalate group is not particularly limited, but is 0.01% by mass or more, preferably 0.05% by mass or more, more preferably 0.1% by mass or more, and 10% by mass or less, preferably 8% by mass or less, more preferably 6% by mass or less, based on the total amount of the nonaqueous electrolyte. The identification and content of the borate having a BF bond and / or an oxalate group are measured by nuclear magnetic resonance (NMR) spectroscopy.
[0032] In the case where two or more kinds of compounds (B) selected from the group consisting of phosphates having a PF bond and a P=O bond, sulfonates having an SF bond, and borates having a BF bond and / or an oxalate group are contained, the total content of the compound (B) is usually 0.01 mass% or more, preferably 0.05 mass% or more, and more preferably 0.1 mass% or more, based on the total amount of the nonaqueous electrolyte solution. , and is usually 10% by mass or less, preferably 8% by mass or less, and more preferably 6% by mass or less.
[0033] [1-3. Electrolytes] <Lithium salt> As the electrolyte in the non-aqueous electrolyte solution, a lithium salt is usually used. The lithium salt is not particularly limited as long as it is known to be used for this purpose, and any lithium salt can be used. Specific examples of the lithium salt include the following:
[0034] Examples include lithium fluoroborates, lithium fluorophosphates, lithium tungstates, lithium carboxylates, lithium sulfonates, lithium imide salts, lithium methide salts, lithium oxalate salts, and fluorine-containing organic lithium salts.
[0035] Among them, the lithium fluoroborates include LiBF4; the lithium fluorophosphates include LiPF6; the lithium sulfonates include CH3SO3Li; the lithium imide salts include LiN(FSO2)(CF3SO2), LiN(CF3SO2)2, LiN(C2F5SO2)2, lithium cyclic 1,2-perfluoroethane disulfonylimide, and lithium cyclic 1,3-perfluoropropane disulfonylimide; and the lithium methide salts include LiC(FSO2)3, LiC(CF 3SO2)3, LiC(C2F5SO2)3; as lithium oxalate salts, lithium monooxalate difluoroborate, lithium bis(oxalate)borate (LiBOB), lithium tetrafluorooxalate phosphate, lithium difluorobis(oxalate)phosphate, lithium tris(oxalate)phosphate; and the like are more preferred because they have the effect of improving low-temperature output characteristics, high-rate charge / discharge characteristics, impedance characteristics, high-temperature storage characteristics, cycle characteristics, and the like. More preferred is LiPF6 or lithium bis(oxalate)borate, and particularly preferred is LiPF6. The above electrolytes may be used alone or in combination of two or more. However, when a lithium salt electrolyte corresponding to the combined additive described in [1-2-1. Phosphate having PF bond and P=O bond] to [1-2-3. Boron having BF bond and / or oxalate group] is contained in the non-aqueous electrolyte, an electrolyte other than the lithium salt corresponding to the combined additive is necessarily contained. The combination of two or more electrolytes is not particularly limited, but preferred examples include a combination of LiPF6 and LiBF4, and a combination of LiPF6 and LiN(CF3SO2)2. Of these, the combination of LiPF6 and LiBF4 is preferred.
[0036] The total concentration of the electrolyte in the non-aqueous electrolyte is not particularly limited, but is usually 8% by mass or more, preferably 8.5% by mass or more, more preferably 9% by mass or more, and is usually 18% by mass or less, preferably 17% by mass or less, more preferably 16% by mass or less, based on the total amount of the non-aqueous electrolyte. If the total concentration of the electrolyte is within the above range, the electrical conductivity becomes appropriate for the battery operation, so that sufficient output characteristics tend to be obtained. The electrolyte is identified and the content is measured by nuclear magnetic resonance (NMR) spectroscopy.
[0037] [1-4. Non-aqueous solvents] The non-aqueous electrolyte according to one embodiment of the present invention, like a general non-aqueous electrolyte, usually contains a non-aqueous solvent that dissolves the above-mentioned electrolyte as its main component. The non-aqueous solvent used is not particularly limited as long as it dissolves the above-mentioned electrolyte, and a known organic solvent can be used. Examples of the organic solvent include, but are not limited to, saturated cyclic carbonates, chain carbonates, chain carboxylate esters (excluding the compound represented by formula (I)), cyclic carboxylate esters, ether compounds, and sulfone compounds. The organic solvent can be used alone or in combination of two or more kinds. The combination of two or more organic solvents is not particularly limited, and examples thereof include saturated cyclic carbonates and chain carboxylates, cyclic carboxylates and chain carbonates, and saturated cyclic carbonates, chain carbonates and chain carboxylates. Among these, saturated cyclic carbonates and chain carbonates, and saturated cyclic carbonates, chain carbonates and chain carboxylates are preferred.
[0038] [1-4-1. Saturated cyclic carbonates] Examples of saturated cyclic carbonates include those having an alkylene group having 2 to 4 carbon atoms, and saturated cyclic carbonates having 2 to 3 carbon atoms are preferably used from the viewpoint of improving battery characteristics resulting from an improvement in the degree of dissociation of lithium ions.
[0039] Specific examples of the saturated cyclic carbonate include ethylene carbonate, propylene carbonate, butylene carbonate, etc. Among them, ethylene carbonate or propylene carbonate is preferred, and ethylene carbonate, which is less susceptible to oxidation and reduction, is more preferred. The saturated cyclic carbonate may be used alone or in any combination and ratio of two or more.
[0040] The content of the saturated cyclic carbonate is not particularly limited and may be any content as long as it does not significantly impair the effects of the present invention, but is usually 3% by volume or more, preferably 5% by volume or more, and is usually 90% by volume or less, preferably 85% by volume or less, and more preferably 80% by volume or less, based on the total amount of the nonaqueous solvent in the nonaqueous electrolyte. By setting the content in this range, a decrease in electrical conductivity due to a decrease in the dielectric constant of the nonaqueous electrolyte is avoided, and the large current discharge characteristics, stability with respect to the negative electrode, and cycle characteristics of the nonaqueous electrolyte secondary battery tend to be in a good range, and the oxidation / reduction resistance of the nonaqueous electrolyte tends to be improved, and the stability during high-temperature storage tends to be improved. In the present embodiment, the volume % refers to the volume at 25° C. and 1 atmospheric pressure.
[0041] [1-4-2. Chain carbonates] As the chain carbonate, one having 3 to 7 carbon atoms is usually used, and in order to adjust the viscosity of the electrolyte solution within an appropriate range, a chain carbonate having 3 to 5 carbon atoms is preferably used.
[0042] Specific examples of the chain carbonate include dimethyl carbonate, diethyl carbonate, di-n-propyl carbonate, diisopropyl carbonate, n-propyl isopropyl carbonate, ethyl methyl carbonate, and methyl-n-propyl carbonate. Dimethyl carbonate, diethyl carbonate, and ethyl methyl carbonate are particularly preferred.
[0043] In addition, chain carbonates having fluorine atoms (hereinafter, sometimes abbreviated as "fluorinated chain carbonate") can also be suitably used. The number of fluorine atoms in the fluorinated chain carbonate is not particularly limited as long as it is 1 or more, but is usually 6 or less, and preferably 4 or less. When the fluorinated chain carbonate has multiple fluorine atoms, the multiple fluorine atoms may be bonded to the same carbon or different carbons. Examples of the fluorinated chain carbonate include fluorinated dimethyl carbonate derivatives such as fluoromethyl methyl carbonate; fluorinated ethyl methyl carbonate derivatives such as 2-fluoroethyl methyl carbonate; and fluorinated diethyl carbonate derivatives such as ethyl-(2-fluoroethyl) carbonate.
[0044] The chain carbonate may be used alone or as a mixture of two or more kinds in any combination and in any ratio.
[0045] The amount of the chain carbonate is not particularly limited, but is preferably about 100% by weight based on the total amount of the non-aqueous solvent in the non-aqueous electrolyte. The content of the chain carbonate is usually 15% by volume or more, preferably 20% by volume or more, more preferably 25% by volume or more, and usually 90% by volume or less, preferably 85% by volume or less, more preferably 80% by volume or less. By setting the content of the chain carbonate in the above range, the viscosity of the nonaqueous electrolyte can be set in an appropriate range, a decrease in ion conductivity can be suppressed, and the output characteristics of the nonaqueous electrolyte secondary battery can be easily set in a good range.
[0046] Furthermore, by combining a specific chain carbonate with ethylene carbonate in a specific content, the battery performance can be significantly improved.
[0047] For example, when dimethyl carbonate and ethyl methyl carbonate are selected as specific chain carbonates, the content of ethylene carbonate is not particularly limited and is arbitrary as long as it does not significantly impair the effects of the present invention according to this embodiment, but it is usually 15% by volume or more, preferably 20% by volume or more, and usually 45% by volume or less, preferably 40% by volume or less, based on the total amount of non-aqueous solvent in the non-aqueous electrolyte solution, the content of dimethyl carbonate is usually 20% by volume or more, preferably 30% by volume or more, and usually 50% by volume or less, preferably 45% by volume or less, based on the total amount of non-aqueous solvent in the non-aqueous electrolyte solution, the content of ethyl methyl carbonate is usually 20% by volume or more, preferably 30% by volume or more, and usually 50% by volume or less, preferably 45% by volume or less, based on the total amount of non-aqueous solvent in the non-aqueous electrolyte solution. By setting the content within the above range, there is a tendency for high temperature stability to be excellent and gas generation to be suppressed.
[0048] [1-4-3. Chain carboxylate esters] Examples of the chain carboxylic acid ester (excluding the compound represented by formula (I)) include: Examples of the carboxylic acid ester include methyl acetate, ethyl acetate, propyl acetate, butyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, methyl valerate, methyl isobutyrate, ethyl isobutyrate, and methyl pivalate. Among them, methyl acetate, ethyl acetate, propyl acetate, and butyl acetate are preferable from the viewpoint of improving battery characteristics. Chain carboxylates in which a part of the hydrogen of the above-mentioned compounds is replaced with a fluorine atom (e.g., methyl trifluoroacetate, ethyl trifluoroacetate, etc.) can also be suitably used. The content of the chain carboxylate is usually 1% by volume or more, preferably 5% by volume or more, more preferably 15% by volume or more, based on the total amount of the nonaqueous solvent. Within this range, the electrical conductivity of the nonaqueous electrolyte is improved, and the large-current discharge characteristics of the nonaqueous electrolyte battery are easily improved. In addition, the content of the chain carboxylate is usually 70% by volume or less, preferably 50% by volume or less, more preferably 40% by volume or less. By setting the upper limit in this way, the viscosity of the nonaqueous electrolyte is kept in an appropriate range, a decrease in electrical conductivity is avoided, an increase in the negative electrode resistance is suppressed, and the large-current discharge characteristics of the nonaqueous electrolyte secondary battery are easily kept in a good range.
[0049] [1-4-4. Cyclic carboxylate esters] Examples of cyclic carboxylates include γ-butyrolactone and γ-valerolactone. Among these, γ-butyrolactone is more preferable. In addition, cyclic carboxylates in which some of the hydrogen atoms of the above-mentioned compounds are replaced with fluorine can also be used. The content of the cyclic carboxylate is usually 1% by volume or more, preferably 5% by volume or more, more preferably 15% by volume or more, based on the total amount of the nonaqueous solvent in the nonaqueous electrolyte. In this range, the electrical conductivity of the nonaqueous electrolyte is improved, and the large-current discharge characteristics of the nonaqueous electrolyte battery are easily improved. In addition, the content of the cyclic carboxylate is usually 70% by volume or less, preferably 50% by volume or less, more preferably 40% by volume or less, based on the total amount of the nonaqueous solvent. By setting the upper limit in this way, the viscosity of the nonaqueous electrolyte is in an appropriate range, the decrease in electrical conductivity is avoided, the increase in the negative electrode resistance is suppressed, and the large-current discharge characteristics of the nonaqueous electrolyte secondary battery are easily in a good range.
[0050] [1-4-5. Ether compounds] The ether-based compound is not particularly limited, but preferable examples include chain ethers having 3 to 10 carbon atoms, such as dimethoxymethane, diethoxymethane, ethoxymethoxymethane, ethylene glycol di-n-propyl ether, ethylene glycol di-n-butyl ether, and diethylene glycol dimethyl ether; and cyclic ethers having 3 to 6 carbon atoms, such as tetrahydrofuran, 2-methyltetrahydrofuran, 3-methyltetrahydrofuran, 1,3-dioxane, 2-methyl-1,3-dioxane, 4-methyl-1,3-dioxane, and 1,4-dioxane. Note that some of the hydrogen atoms in the above-mentioned ether-based compounds may be substituted with fluorine. Among these, as the chain ether having 3 to 10 carbon atoms, dimethoxymethane, diethoxymethane, and ethoxymethoxymethane are preferred because they have a high solvation ability for lithium ions, improve ion dissociation, have low viscosity, and provide high ionic conductivity, and as the cyclic ether having 3 to 6 carbon atoms, tetrahydrofuran, 1,3-dioxane, 1,4-dioxane, and the like are preferred because they provide high ionic conductivity.
[0051] The content of the ether-based compound is not particularly limited, and may be any content as long as it does not significantly impair the effects of the present invention according to this embodiment. However, it is usually 1% by volume or more, preferably 2% by volume or more, more preferably 3% by volume or more, and usually 30% by volume or less, preferably 25% by volume or less, more preferably 20% by volume or less, based on the total amount of the nonaqueous solvent in the nonaqueous electrolyte. If the content of the ether-based compound is within the above range, it is easy to ensure the effect of improving the degree of lithium ion dissociation and improving the ion conductivity due to the viscosity reduction. In addition, when the negative electrode active material is a carbon-based material, the phenomenon in which the chain ether is co-inserted with the lithium ion can be suppressed, so that the input / output characteristics and the charge / discharge rate characteristics can be set to an appropriate range.
[0052] [1-4-6. Sulfone compounds] The sulfone compound is not particularly limited, and may be a cyclic sulfone or a chain sulfone. In the case of a cyclic sulfone, the carbon number is usually 3 to 6, preferably 3 to 5, and in the case of a chain sulfone, the carbon number is usually 2 to 6, preferably 2 to 5. In addition, the number of sulfonyl groups in one molecule of the sulfone compound is not particularly limited, but is usually 1 or 2.
[0053] Examples of cyclic sulfones include monosulfone compounds such as trimethylene sulfones, tetramethylene sulfones, hexamethylene sulfones, etc., and disulfone compounds such as trimethylene disulfones, tetramethylene disulfones, hexamethylene disulfones, etc. Among these, from the viewpoint of dielectric constant and viscosity, tetramethylene sulfones, tetramethylene disulfones, hexamethylene sulfones, or hexamethylene disulfones are more preferred, and tetramethylene sulfones (sulfolanes) are particularly preferred.
[0054] As the sulfolanes, sulfolane and sulfolane derivatives are preferred, and as the sulfolane derivatives, those in which one or more hydrogen atoms bonded to the carbon atoms constituting the sulfolane ring are substituted with a fluorine atom, an alkyl group, or a fluorine-substituted alkyl group are preferred.
[0055] Among these, 2-methylsulfolane, 3-methylsulfolane, 2-fluorosulfolane, 3-fluorosulfolane, 2,3-difluorosulfolane, 2-trifluoromethylsulfolane, 3-trifluoromethylsulfolane, and the like are preferred because they have high ionic conductivity and high input / output.
[0056] Examples of the chain sulfone include dimethyl sulfone, ethyl methyl sulfone, diethyl sulfone, monofluoromethyl methyl sulfone, difluoromethyl methyl sulfone, trifluoromethyl methyl sulfone, pentafluoroethyl methyl sulfone, etc. Among these, dimethyl sulfone, ethyl methyl sulfone, and monofluoromethyl methyl sulfone are preferred in terms of improving the high-temperature storage stability of the electrolyte.
[0057] The content of the sulfone-based compound is not particularly limited, and may be any as long as it does not significantly impair the effect of the present invention according to this embodiment, but is usually 0.3% by volume or more, preferably 0.5% by volume or more, more preferably 1% by volume or more, and is usually 40% by volume or less, preferably 35% by volume or less, more preferably 30% by volume or less, based on the total amount of the non-aqueous solvent in the non-aqueous electrolyte. If the content of the sulfone-based compound is within the above range, an electrolyte having excellent high-temperature storage stability tends to be obtained.
[0058] [1-5. Auxiliaries] The non-aqueous electrolyte of the present invention may contain various auxiliary agents within the range that does not significantly impair the effects of the present invention. As the auxiliary agent, any conventionally known one may be used. In addition, the auxiliary agent may be used alone, or two or more kinds may be used in any combination and ratio.
[0059] Examples of auxiliary agents that may be contained in the non-aqueous electrolyte solution include cyclic carbonates having a carbon-carbon unsaturated bond, fluorine-containing cyclic carbonates, compounds having an isocyanate group, compounds having an isocyanuric acid skeleton, sulfur-containing organic compounds, phosphorus-containing organic compounds, organic compounds having a cyano group, silicon-containing compounds, aromatic compounds, non-fluorine-containing carboxylic acid esters, cyclic compounds having an ether bond, carboxylic acid anhydrides, borates (excluding borates having a BF bond and / or an oxalate group), oxalate salts (excluding borates having a BF bond and / or an oxalate group), and the like. and / or borates having an oxalate group.) Examples of the compound include those described in JP-A-2015 / 111676. The cyclic compound having an ether bond can be used as an auxiliary in a non-aqueous electrolyte, and as shown in 1-4, it can also be used as a non-aqueous solvent. When using a cyclic compound having an ether bond as an auxiliary, it is used in an amount of less than 4 mass%. When using a borate or an oxalate as an auxiliary in a non-aqueous electrolyte, it can also be used as an electrolyte, as shown in 1-3. When using a borate or an oxalate as an auxiliary, it is used in an amount of less than 3 mass%.
[0060] [2. Non-aqueous electrolyte secondary battery] A nonaqueous electrolyte secondary battery according to one embodiment of the present invention is a nonaqueous electrolyte secondary battery including a positive electrode having a positive electrode active material capable of absorbing and releasing metal ions, and a negative electrode having a negative electrode active material capable of absorbing and releasing metal ions, and contains a nonaqueous electrolyte.
[0061] [2-1. Non-aqueous electrolyte] As the non-aqueous electrolyte solution, the above-mentioned non-aqueous electrolyte solution is used. Note that, within the scope of the present invention, it is also possible to mix the above-mentioned non-aqueous electrolyte solution with other non-aqueous electrolyte solutions.
[0062] [2-2. Negative electrode] The negative electrode has a negative electrode active material on at least a portion of the surface of a current collector. [2-2-1. Negative electrode active material] The negative electrode active material used in the negative electrode is not particularly limited as long as it can electrochemically absorb and release metal ions. Specific examples include carbon-based materials, materials containing metal elements and / or metalloid elements that can be alloyed with Li, lithium-containing metal composite oxide materials, and mixtures thereof. Among these, it is preferable to use a carbon-based material, a material containing metal elements and / or metalloid elements that can be alloyed with Li, or a mixture of particles of a material containing metal elements and / or metalloid elements that can be alloyed with Li and graphite particles, in terms of good cycle characteristics and safety and excellent continuous charging characteristics. These may be used alone or in any combination of two or more.
[0063] [2-2-2. Carbon-based materials] Examples of carbonaceous materials include natural graphite, artificial graphite, amorphous carbon, carbon-coated graphite, graphite-coated graphite, and resin-coated graphite. Of these, natural graphite is preferred. The carbonaceous materials may be used alone or in any combination and ratio of two or more. Examples of natural graphite include scaly graphite, scaly graphite, and / or graphite particles obtained by subjecting these to treatments such as spheroidization, densification, etc. Among these, from the viewpoint of particle packing properties or charge / discharge rate characteristics, spherical or ellipsoidal graphite particles that have been subjected to a spheroidization treatment are particularly preferred. The average particle size (d50) of the graphite particles is usually 1 μm or more and 100 μm or less.
[0064] [2-2-3. Properties of carbon-based materials] The carbonaceous material as the negative electrode active material preferably satisfies at least one of the characteristics such as the physical properties and shape shown in the following (1) to (4), and particularly preferably satisfies several of them at the same time. (1) X-ray diffraction parameters The d value (interlayer distance) of the lattice plane (002 plane) of carbon-based materials determined by X-ray diffraction using the Gakushin method is usually 0.335 nm or more and 0.360 nm or less. In addition, the crystallite size (Lc) of carbon-based materials determined by X-ray diffraction using the Gakushin method is usually 1.0 nm or more. (2) Volume-based average particle size The volume-based average particle size of a carbon-based material is the volume-based average particle size (median diameter) determined by a laser diffraction / scattering method, and is usually 1 μm or more and 100 μm or less. (3) Raman R value, Raman half-width The Raman R value of a carbon-based material is a value measured using argon ion laser Raman spectroscopy, and is usually 0.01 or more and 1.5 or less. In addition, the 1580 cm -1 The Raman half-width in the vicinity is not particularly limited, but is usually 10 cm -1 More than 100cm -1 The following is the result. (4) BET specific surface area The BET specific surface area of a carbon-based material is the value of the specific surface area measured using the BET method, and is usually 0.1 m 2 ·g -1 More than 100m 2 ·g -1 The following is the result. The negative electrode active material may contain two or more carbonaceous materials with different properties, where the properties refer to X-ray diffraction parameters, volume-based average particle size, Raman R value, Raman half-width, or BET specific surface area. Preferred examples include a case in which the volume-based particle size distribution is not symmetrical about the median size, a case in which two or more carbon-based materials having different Raman R values are contained, and a case in which two or more carbon-based materials having different X-ray parameters are contained.
[0065] [2-2-4. Materials containing metallic elements and / or semi-metallic elements that can be alloyed with Li] Any conventionally known material containing a metal element and / or a metalloid element capable of being alloyed with Li can be used, but in terms of capacity and cycle life, it is preferable that the material is, for example, a simple substance of a metal and / or a metalloid element selected from the group consisting of Sb, Si, Sn, Al, As, and Zn, or a compound thereof. In addition, when the material containing a metal element and / or a metalloid element capable of being alloyed with Li contains two or more kinds of metal elements, the material may be an alloy material made of an alloy of these elements. Examples of materials containing a metal element and / or a metalloid element that can be alloyed with Li include oxides, nitrides, carbides, etc. These may contain two or more types of metal elements and / or metalloid elements that can be alloyed with Li. Among these, metal Si (hereinafter sometimes referred to as Si) or a compound containing Si is preferred in terms of increasing capacity.
[0066] In this specification, Si or Si-containing compounds are collectively referred to as Si compounds. Specific examples of Si compounds include SiO x , SiN x , SiC x , SiZ x‘ Oy (Z=C, N) etc. Examples of the Si compounds include Si oxide (SiO x ) is preferred because it has a larger theoretical capacity than graphite, and amorphous Si or nano-sized Si crystals are preferred because they allow alkali ions such as lithium ions to easily enter and exit the material, making it possible to obtain a high capacity. This general formula SiO x The silicon oxide represented by the formula is obtained from silicon dioxide (SiO2) and silicon, and the value of x is usually 0. <x<2である。 When the material containing a metallic element and / or a metalloid element capable of being alloyed with Li is in the form of particles, the average particle size (d50) is usually 0.01 μm or more and 10 μm or less from the viewpoint of cycle life.
[0067] [2-2-5. Mixture of particles of material containing metallic and / or semi-metallic elements capable of being alloyed with Li and graphite particles] The mixture of graphite particles and particles of a material containing a metal element and / or a metalloid element capable of being alloyed with Li used as the negative electrode active material may be a mixture in which the particles containing the above-mentioned metal element and / or metalloid element capable of being alloyed with Li and the above-mentioned graphite particles are mixed in the state of independent particles, or it may be a composite in which particles of a material containing a metal element and / or a metalloid element capable of being alloyed with Li are present on the surface or inside of graphite particles. The content ratio of particles of a material containing a metal element and / or a metalloid element that can be alloyed with Li to the total of particles of a material containing a metal element and / or a metalloid element that can be alloyed with Li and graphite particles is typically 1 mass% or more and 99 mass% or less.
[0068] [2-2-6. Lithium-containing metal composite oxide materials] The lithium-containing metal composite oxide material used as the negative electrode active material is not particularly limited as long as it is capable of absorbing and releasing lithium ions. From the viewpoint of high current density charge / discharge characteristics, however, a lithium-containing metal composite oxide material containing titanium is preferable, a composite oxide of lithium and titanium (hereinafter sometimes abbreviated as "lithium titanium composite oxide") is more preferable, and a lithium titanium composite oxide having a spinel structure is particularly preferable since it greatly reduces the output resistance.
[0069] Furthermore, the lithium and / or titanium of the lithium titanium composite oxide may be substituted with another metal element, for example, at least one element selected from the group consisting of Al, Ga, Cu and Zn. Lithium titanium composite oxide, Li 4 / 3 Ti 5 / 3 O4, Li1Ti2O4 and Li 4 / 5 Ti 11 / 5 O4 is preferred. In addition, examples of lithium titanium composite oxides in which part of lithium and / or titanium is replaced with other elements include Li 4 / 3 Ti 4 / 3 Al 1 / 3 O4 is preferred.
[0070] [2-2-7. Negative electrode structure and preparation method] The negative electrode may be produced by any known method as long as it does not significantly impair the effects of the present invention. For example, the negative electrode may be produced by adding a binder, a solvent, and, if necessary, a thickener, a conductive material, a filler, etc. to the negative electrode active material to form a slurry, which is then applied to a current collector, dried, and pressed to form a negative electrode active material layer.
[0071] [2-2-7-1. Current collector] Any known current collector can be used to hold the negative electrode active material. Examples of the current collector for the negative electrode include metal materials such as aluminum, copper, nickel, stainless steel, and nickel-plated steel, and copper is particularly preferred from the standpoints of ease of processing and cost. The shape of the current collector may be, for example, a metal foil, a metal cylinder, a metal coil, a metal plate, a metal thin film, an expanded metal, a punched metal, a foamed metal, or the like. Among these, a metal thin film or a metal foil is preferred. Copper foil is more preferred, and rolled copper foil produced by a rolling method and electrolytic copper foil produced by an electrolytic method are even more preferred. The metal thin film and metal foil are suitably shaped into a mesh. It may be possible to do so. When the negative electrode current collector has a plate or film shape, the current collector may have any thickness, but it is usually 1 μm or more and 1 mm or less.
[0072] [2-2-7-2. Binder] There are no particular limitations on the binder that binds the negative electrode active material, so long as it is a material that is stable to the non-aqueous electrolyte solution and the solvent used in producing the electrode. Specific examples include rubber-like polymers such as SBR (styrene-butadiene rubber), isoprene rubber, butadiene rubber, fluororubber, NBR (acrylonitrile-butadiene rubber), and ethylene-propylene rubber; fluorine-based polymers such as polyvinylidene fluoride, polytetrafluoroethylene, and tetrafluoroethylene-ethylene copolymers. These may be used alone or in any combination and ratio of two or more. The ratio of the binder to the negative electrode active material is usually 0.1 mass % or more and 20 mass % or less. In particular, when the binder contains a rubber-like polymer such as SBR as a main component, the ratio of the binder to the negative electrode active material is preferably 0.1% by mass or more and 5% by mass or less. Also, when the binder contains a fluorine-based polymer such as polyvinylidene fluoride as a main component, the ratio of the binder to the negative electrode active material is preferably 1% by mass or more and 15% by mass or less.
[0073] [2-2-7-3. Solvent] The solvent for forming the slurry is not particularly limited as long as it is capable of dissolving or dispersing the negative electrode active material, the binder, and the thickener, conductive material, filler, and the like that are used as needed, and either an aqueous solvent or an organic solvent may be used.
[0074] [2-2-7-4. Thickener] The thickener is usually used to adjust the viscosity of the slurry. The thickener is not particularly limited, but specifically includes carboxymethyl cellulose, methyl cellulose, hydroxymethyl cellulose, ethyl cellulose, polyvinyl alcohol, etc. These may be used alone or in any combination and ratio of two or more. When a thickener is used, the ratio of the thickener to the negative electrode active material is usually 0.1 mass % or more and 5 mass % or less.
[0075] [2-2-8. Electrode density] There are no particular restrictions on the structure of the electrode when the negative active material is made into an electrode, but the density of the negative active material on the current collector is usually 1 g cm -3 More than 2.2g cm -3 The following is the result.
[0076] [2-2-9. Thickness of negative electrode plate] The thickness of the negative electrode (also referred to as "negative electrode plate") is designed to match the positive electrode (also referred to as "positive electrode plate") used and is not particularly limited, but the thickness of the negative electrode active material layer obtained by subtracting the thickness of the current collector from the thickness of the negative electrode plate is usually 15 μm or more and 300 μm or less.
[0077] [2-2-10. Surface coating of negative electrode plate] The negative electrode plate may have a surface to which a substance having a different composition from the negative electrode active material (surface-attached substance) is attached. Examples of the surface-attached substance include oxides such as aluminum oxide, sulfates such as lithium sulfate, and carbonates such as lithium carbonate.
[0078] [2-3. Positive electrode] The positive electrode has a positive electrode active material on at least a portion of the surface of a current collector. [2-3-1. Positive electrode active material] The positive electrode active material (lithium transition metal compound) used in the positive electrode will be described below.
[0079] [2-3-1-1. Lithium transition metal compounds] The lithium transition metal compound is a compound having a structure capable of desorbing and inserting lithium ions, and examples thereof include sulfides, phosphate compounds, silicate compounds, borate compounds, lithium transition metal composite oxides, etc. Among these, phosphate compounds and lithium transition metal composite oxides are preferred, and lithium transition metal composite oxides are more preferred. Examples of lithium transition metal composite oxides include those having a spinel structure that allows three-dimensional diffusion, and those having a layered structure that allows two-dimensional diffusion of lithium ions. Those having a spinel structure are generally represented by the following composition formula (1). Li x M2O4···(1) (In formula (1), x is 1≦x≦1.5, and M represents one or more transition metal elements.) Specifically, LiMn2O4, LiCoMnO4, LiNi 0.5 Mn 1.5 O4, LiCoVO4, etc. Those having a layered structure are generally represented by the following composition formula (2). Li x’ M'O2···(2) (In formula (2), x' is -0.1≦x'≦0.5, and M' represents one or more transition metal elements.) Specifically, LiCoO2, LiNiO2, LiNi 0.85 Co 0.10 Al 0.05 O2, LiNi 0.80 Co 0.15 Al 0.05 O2, LiNi 0.33 Co 0.33 Mn 0.33 O2, Li 1.05 Ni 0.33 Co 0.33 Mn 0.33 O2, LiNi 0.5 Co 0.2 Mn 0.3 O2, Li 1.05 Ni 0.5 Co 0.2 Mn 0.3 O2, LiNi0.6 Co 0.2 Mn 0.2 O2, LiNi 0.8 Co 0.1 Mn 0.1 Examples include O2.
[0080] Among these, from the viewpoint of improving the battery capacity, a lithium transition metal composite oxide having a layered structure is preferred, and a lithium transition metal composite oxide represented by the following composition formula (3) is more preferred. Li a1 Ni b1 M' c1 O2···(3) (In formula (3), a1, b1, and c1 are numerical values that satisfy 0.90≦a1≦1.10, 0.30≦b1≦0.98, and 0.00≦c1≦0.50, respectively, and b1+c1=1 is satisfied. M' represents one or more elements selected from the group consisting of Co, Mn, Al, Mg, Zr, Fe, Ti, and Er.)
[0081] In particular, a lithium transition metal composite oxide represented by the following composition formula (4) is preferable. Li a2 Ni b2 Co c2 M' d2 O2···(4) (In formula (4), a2, b2, c2, and d2 are numerical values that satisfy 0.90≦a2≦1.10, 0.33≦b2≦0.98, 0.01≦c2<0.50, and 0.01≦d2<0.50, respectively, and b2+c2+d2=1 is satisfied. M' represents one or more elements selected from the group consisting of Mn, Al, Mg, Zr, Fe, Ti, and Er.) In the composition formula (4), d2 is preferably a number that satisfies 0.10≦d2≦0.50.
[0082] A specific example of the lithium transition metal composite oxide represented by the composition formula (4) is LiNi 0.85 Co 0.10 Al 0.05 O2, LiNi 0.80 Co 0.15 Al 0.05 O2, LiNi0.5 Co 0.2 Mn 0.3 O2, Li 1.05 Ni 0.50 Co 0.20 Mn 0.30 O2, LiNi 0.6 Co 0.2 Mn 0.2 O2, LiNi 0.8 Co 0.1 Mn 0.1 O2, Li 1.05 Ni 0.34 Mn 0.33 Co 0.33 O2, etc.
[0083] In each composition formula, M' preferably contains Mn or Al, and more preferably contains Mn. It is more preferable that the lithium-transition metal composite oxide is made of Mn or Al, because this increases the structural stability of the lithium-transition metal composite oxide and suppresses structural deterioration during repeated charge and discharge.
[0084] [2-3-1-2. Introduction of different elements] Furthermore, elements (foreign elements) other than the elements contained in the above composition formula may be incorporated into the lithium transition metal composite oxide.
[0085] [2-3-1-3. Surface coating] The positive electrode active material may have a surface-attached substance having a different composition from the positive electrode active material. Examples of the surface-attached substance include oxides such as aluminum oxide, sulfates such as lithium sulfate, and carbonates such as lithium carbonate. These surface-adhering substances can be attached to the surface of the positive electrode active material, for example, by dissolving or suspending them in a solvent, adding them to the positive electrode active material by impregnation, and drying them. The amount of the surface-attaching substance is preferably 1 μmol / g or more, more preferably 10 μmol / g or more, and is usually 1 mmol / g or less, relative to the positive electrode active material. In this specification, a positive electrode active material having the above-mentioned surface-adhering substance attached to the surface thereof is also referred to as a "positive electrode active material".
[0086] [2-3-1-4. Blend] These positive electrode active materials may be used alone or in any combination of two or more in any ratio.
[0087] [2-3-2. Positive electrode composition and manufacturing method] The configuration and manufacturing method of the positive electrode are described below. In this embodiment, the positive electrode using the positive electrode active material can be manufactured by a conventional method. That is, the positive electrode active material and the binder, and if necessary, the conductive material and the thickener, etc. are mixed in a dry state to form a sheet, which is then pressed onto the positive electrode current collector, or these materials are dissolved or dispersed in a liquid medium to form a slurry, which is then applied to the positive electrode current collector and dried to form a positive electrode active material layer on the current collector, thereby obtaining a positive electrode by a coating method. In addition, for example, the above-mentioned positive electrode active material may be roll-formed into a sheet electrode, or may be compression-formed into a pellet electrode. Hereinafter, the case where the slurry is successively applied to the positive electrode current collector and then dried will be described.
[0088] [2-3-2-1. Active material content] The content of the positive electrode active material in the positive electrode active material layer is usually 80% by mass or more and 98% by mass or less.
[0089] [2-3-2-2.Conductive materials] Any known conductive material can be used as the conductive material. Specific examples include metal materials such as copper and nickel; carbon-based materials such as natural graphite, graphite, and carbon black; and the like. The conductive material may be used alone or in any combination and ratio of two or more. The conductive material is used so that it is usually contained in the positive electrode active material layer in an amount of 0.01 mass % or more and 50 mass % or less.
[0090] [2-3-2-3. Binder] The binder used in producing the positive electrode active material layer is not particularly limited as long as it is a material that is dissolved or dispersed in a liquid medium for a slurry, for example, when the positive electrode active material layer is formed by a coating method. In view of weather resistance, chemical resistance, heat resistance, flame retardancy, and the like, preferred are fluorine-based resins such as polyvinyl fluoride, polyvinylidene fluoride, and polytetrafluoroethylene; CN group-containing polymers such as polyacrylonitrile and polyvinylidene cyanide; and the like. In addition, mixtures, modified products, derivatives, random copolymers, and alternating copolymers of the above polymers are also usable. It is also possible to use copolymers, graft copolymers, block copolymers, etc. The binder may be used alone or in any combination and ratio of two or more kinds. Furthermore, when a resin is used as a binder, the weight average molecular weight of the resin is optional as long as it does not significantly impair the effects of the present invention, but is usually from 10,000 to 3,000,000. When the molecular weight is in this range, the strength of the electrode is improved, and the electrode can be suitably formed. The proportion of the binder in the positive electrode active material layer is usually 0.1 mass % or more and 80 mass % or less.
[0091] [2-3-2-4.Liquid medium] The liquid medium for forming the slurry is not particularly limited in type as long as it is a solvent capable of dissolving or dispersing the positive electrode active material, the conductive material, the binder, and the thickener used as needed, and either an aqueous solvent or an organic solvent may be used.
[0092] [2-3-2-5. Current collector] The material of the positive electrode current collector is not particularly limited, and any known material can be used. Specific examples include metal materials such as aluminum, stainless steel, nickel plating, titanium, and tantalum. Among them, aluminum is preferable. The shape of the current collector may be metal foil, metal cylinder, metal coil, metal plate, metal thin film, expanded metal, punched metal, foamed metal, etc. Among these, metal foil or metal thin film is preferable. The metal foil and metal thin film may be appropriately formed into a mesh shape. When the positive electrode current collector has a plate or film shape, the current collector may have any thickness, but it is usually 1 μm or more and 1 mm or less.
[0093] [2-3-2-6. Thickness of positive electrode plate] The thickness of the positive electrode plate is not particularly limited, but from the viewpoint of high capacity and high output, the thickness of the positive electrode active material layer obtained by subtracting the thickness of the current collector from the thickness of the positive electrode plate is usually 10 μm or more and 500 μm or less on one side of the current collector.
[0094] [2-3-2-7. Density of the positive electrode active material layer] The positive electrode active material layer obtained by coating and drying is preferably compressed by a hand press, a roller press, or the like in order to increase the packing density of the positive electrode active material. The density of the positive electrode active material layer present on the current collector is usually 1.5 g / cm 3 More than 4.5g / cm 3 The following is the result.
[0095] [2-3-2-8. Surface coating of positive electrode plate] In addition, the positive electrode plate may have a substance having a different composition from that of the positive electrode plate attached to its surface, and the substance in question may be the same substance as the surface-attached substance that may be attached to the surface of the positive electrode active material.
[0096] [2-4. Separator] A separator is usually interposed between the positive electrode and the negative electrode to prevent short circuiting. In this case, the non-aqueous electrolyte is usually impregnated into the separator before use.
[0097] [2-4-1. Materials] The material of the separator is not particularly limited as long as it is stable against the non-aqueous electrolyte, but preferably includes, for example, oxides such as alumina and silicon dioxide, nitrides such as aluminum nitride and silicon nitride, sulfates such as barium sulfate and calcium sulfate, inorganic materials such as glass filters made of glass fibers, and resins such as polyolefins, more preferably polyolefins, and particularly preferably polyethylene or polypropylene. One of these materials may be used alone, or two or more may be used in any combination and ratio. The above materials may also be used in a laminated state.
[0098] [2-4-2.Form] The form of the separator is not particularly limited, but preferably, a thin film such as a nonwoven fabric, a woven fabric, or a microporous film is used. In the thin film form, a pore size of 0.01 to 1 μm and a thickness of 1 to 50 μm are preferably used. In addition to an independent thin film form, a separator may be used in which a composite porous layer containing inorganic particles is formed on the surface layer of the positive electrode and / or negative electrode using a resin binder. The form of the separator is preferably a microporous film or a nonwoven fabric because it has excellent liquid retention.
[0099] [2-4-3. Porosity] When a porous material such as a porous sheet or nonwoven fabric is used as the separator, the porosity of the separator is not limited, but is usually 20% or more and 90% or less.
[0100] [2-4-4. Air permeability] The air permeability of a separator in a non-aqueous electrolyte secondary battery can be understood by its Gurley value. The Gurley value indicates the difficulty of air passing through in the film thickness direction, and is expressed as the number of seconds required for 100 mL of air to pass through the film. The Gurley value of a separator is arbitrary, but is usually 10 to 1000 seconds / 100 mL.
[0101] [2-5.Battery design] [2-5-1. Electrode group] The electrode group may be either a laminated structure of the positive electrode plate and the negative electrode plate with the separator interposed therebetween, or a structure of the positive electrode plate and the negative electrode plate wound in a spiral shape with the separator interposed therebetween. The ratio of the volume of the electrode group to the internal volume of the battery (hereinafter referred to as the electrode group occupancy rate) is usually 40% or more and 90% or less.
[0102] [2-5-2. Current collection structure] In the case where the electrode group has the above-mentioned laminated structure, a structure in which the metal core parts of the electrode layers are bundled and welded to a terminal is preferably used. A structure in which multiple terminals are provided in the electrode to reduce resistance is also preferably used. In the case where the electrode group has the above-mentioned wound structure, the internal resistance can be reduced by providing multiple lead structures on each of the positive electrode and the negative electrode and bundling them to a terminal.
[0103] [2-5-3.Protection elements] The protective element may be a PTC (Positive Temperature Coefficient) element whose resistance increases with heat generation due to excessive current, a thermal fuse, a thermistor, a valve (current cutoff valve) that cuts off the current flowing through the circuit due to a sudden increase in the battery's internal pressure or temperature during abnormal heat generation, etc. It is preferable to select the above protective element so that it will not operate under normal use at high current, and it is even more preferable to design it so that abnormal heat generation or thermal runaway does not occur even without the protective element.
[0104] [2-5-4. Exterior body] A non-aqueous electrolyte secondary battery is usually constructed by housing the above-mentioned non-aqueous electrolyte, negative electrode, positive electrode, separator, etc. in an exterior body (exterior case). There are no limitations on this exterior body, and any known exterior body can be used as long as it does not significantly impair the effects of the present invention. The material of the exterior case is not particularly limited as long as it is a substance that is stable to the non-aqueous electrolyte solution used, but from the viewpoint of weight reduction, metal such as aluminum or an aluminum alloy, or a laminate film is preferably used. Examples of exterior cases using the above metals include those in which the metals are welded together by laser welding, resistance welding, or ultrasonic welding to form a sealed, airtight structure, and those in which the above metals are used with a resin gasket in between to form a crimped structure.
[0105] [2-5-5. Shape] The shape of the exterior case is also arbitrary, and may be, for example, cylindrical, rectangular, laminated, coin-shaped, large, or the like. EXAMPLES
[0106] Next, specific embodiments of the present invention will be described in more detail with reference to examples, but the present invention is not limited to these examples. The compounds used in the present examples and comparative examples are shown below.
[0107] [ka]
[0108] [Examples 1-1 to 1-3, Comparative Examples 1-1 to 1-5] [Preparation of non-aqueous electrolyte secondary battery] <Preparation of non-aqueous electrolyte> In a dry argon atmosphere, a non-aqueous electrolyte solution was prepared by dissolving thoroughly dried LiPF6 at 1.0 mol / L (12.3 mass%, as the concentration in the non-aqueous electrolyte solution) in a mixture of ethylene carbonate, ethyl methyl carbonate, and dimethyl carbonate (volume ratio 3:4:3) as a reference electrolyte solution, and an ester compound having a carbon-carbon unsaturated bond (shown as "ester compound" in the table) and a combined additive were dissolved in the non-aqueous electrolyte solution as shown in Table 1 to prepare the non-aqueous electrolyte solutions of Examples 1-1 to 1-3 and Comparative Examples 1-2 to 1-5. The non-aqueous electrolyte solution of Comparative Example 1-1 was the reference electrolyte solution.
[0109] <Preparation of positive electrode> Li as the positive electrode active material 1.05 Ni 0.34 Mn 0.33 Co 0.3385 parts by mass of O2, 10 parts by mass of acetylene black as a conductive material, and 5 parts by mass of polyvinylidene fluoride (PVdF) as a binder were mixed in N-methyl-2-pyrrolidone to form a slurry. This was uniformly applied to an aluminum foil with a thickness of 15 μm, dried, and then roll-pressed to form a positive electrode. The density of the positive electrode active material layer was 2.6 g / cm 3 It was.
[0110] <Preparation of negative electrode> 49 parts by mass of graphite powder was mixed with 50 parts by mass of an aqueous dispersion of sodium carboxymethylcellulose (concentration of sodium carboxymethylcellulose: 1% by mass) as a thickener and 1 part by mass of an aqueous dispersion of styrene-butadiene rubber (concentration of styrene-butadiene rubber: 49% by mass) as a binder, and mixed with a disperser to form a slurry. The obtained slurry was uniformly applied to a copper foil with a thickness of 10 μm, dried, and then roll-pressed to form a negative electrode.
[0111] <Manufacture of non-aqueous electrolyte secondary battery> The positive electrode, the negative electrode, and the polyolefin separator were laminated in this order, and the battery element thus obtained was wrapped in an aluminum laminate film, and the nonaqueous electrolyte was injected and then vacuum sealed to prepare a sheet-shaped nonaqueous electrolyte secondary battery.
[0112] [Evaluation of non-aqueous electrolyte secondary batteries] The nonaqueous electrolyte secondary battery prepared by the above procedure was evaluated as follows. -DCR retention evaluation In a thermostatic bath at 25°C, a sheet-shaped nonaqueous electrolyte secondary battery was charged at a constant current of 0.025C (the current value at which the rated capacity based on the discharge capacity at a 1-hour rate is discharged in 1 hour is defined as 1C; the same applies below) to 3.6V, then charged at a constant current / constant voltage of 0.167C to a voltage of 4.2V, and then discharged at a constant current of 0.167C to 2.5V. Furthermore, the non-aqueous electrolyte secondary battery was stabilized by charging at a constant current and constant voltage at 0.167C to 4.1V, and then storing at 60°C for 12 hours. Thereafter, the battery was discharged at a constant current to 2.5V at 25°C, and then charged at a constant current and constant voltage to a voltage of 4.2V at 0.167C. Thereafter, the battery was discharged at a constant current to 2.5V at 0.167C. Thereafter, the battery was charged at a constant current and constant voltage to 3.7V at 0.167C, and then discharged at a constant current for 10 seconds at 0.5C, 1.0C, and 1.5C, and the initial DCR was obtained from the voltage and current. Next, the battery was charged at a constant current and constant voltage to a voltage of 4.2V at 0.2C, and the initial charge and discharge were completed. The non-aqueous electrolyte secondary battery after the above initial charge and discharge was left at 60°C for 14 days. After leaving it for 14 days, it was discharged at a constant current to 2.5V at 25°C, then charged at a constant current-constant voltage of 0.167C to 3.7V, and then discharged at constant currents of 0.5C, 1.0C, and 1.5C for 10 seconds, and the DCR after storage was calculated from the voltage and current. The DCR retention rate was calculated by dividing the DCR after storage by the initial DCR. The results are shown in Table 1. The DCR retention rates in Table 1 are values normalized with Comparative Example 1-1 set to 100. It can be said that the smaller the DCR retention rate, the more preferable it is.
[0113] [Table 1]
[0114] From Table 1, when Examples 1-1 to 1-3 are compared with Comparative Examples 1-1 to 1-5, it can be seen that the DCR maintenance rate of the nonaqueous electrolyte secondary battery is improved by containing both an ester compound having an unsaturated bond and a phosphate having a PF bond and a P=O bond in the nonaqueous electrolyte. Therefore, it can be seen that the nonaqueous electrolyte of the present invention can specifically improve the battery performance by containing both an ester compound having an unsaturated bond and a phosphate having a PF bond and a P=O bond. In particular, by the combination of Compound 1 and a phosphate having a PF bond and a P=O bond. The reason why the suppression of the DCR increase was most remarkable is thought to be that Compound 1 has a molecular three-dimensionality that moderately interacts with a phosphate having a PF bond and a P=O bond, so that excessive reaction on the electrode can be suppressed.
[0115] [Examples 2-1 to 2-4, Comparative Examples 2-1 to 2-2] [Preparation of non-aqueous electrolyte secondary battery] <Preparation of non-aqueous electrolyte> In a dry argon atmosphere, a nonaqueous electrolyte solution was prepared by dissolving thoroughly dried LiPF6 at 1.0 mol / L (12.3 mass%, as the concentration in the nonaqueous electrolyte solution) in a mixture of ethylene carbonate, ethyl methyl carbonate, and dimethyl carbonate (volume ratio 3:4:3) to prepare a reference electrolyte solution. As shown in Table 2, an ester compound and a concomitant additive were dissolved in the nonaqueous electrolyte solution to prepare the nonaqueous electrolyte solutions of Examples 2-1 to 2-4 and Comparative Examples 2-1 to 2-2.
[0116] <Preparation of positive electrode> Positive electrodes were prepared and used in the same manner as in Examples 1-1 to 1-3 and Comparative Examples 1-1 to 1-5.
[0117] <Preparation of negative electrode> Negative electrodes were prepared and used in the same manner as in Examples 1-1 to 1-3 and Comparative Examples 1-1 to 1-5.
[0118] <Manufacture of non-aqueous electrolyte secondary battery> The positive electrode, the negative electrode, and the polyolefin separator were laminated in this order, and the battery element thus obtained was wrapped in an aluminum laminate film, and the nonaqueous electrolyte was injected and then vacuum sealed to prepare a sheet-shaped nonaqueous electrolyte secondary battery.
[0119] [Evaluation of non-aqueous electrolyte secondary batteries] The nonaqueous electrolyte secondary batteries produced in Examples 2-1 to 2-4 and Comparative Examples 2-1 to 2-2 were evaluated in the same manner as in Examples 1-1 to 1-3 and Comparative Examples 1-1 to 1-5. The results are shown in Table 2. The DCR retention rates in Table 2 are normalized values assuming that Comparative Example 1-1 is 100.
[0120] [Table 2]
[0121] As seen from Table 1, the battery characteristics were significantly improved by co-adding Compound 1 with a phosphate having a PF bond and a P=O bond, and therefore co-addition of Compound 1 with various salts was examined in Table 2. A comparison of Examples 2-1 to 2-4 with Comparative Examples 2-1 to 2-2 shows that the simultaneous inclusion of a specific co-additive can specifically suppress the increase in DCR. These results show that the nonaqueous electrolyte solution of the present invention can specifically improve battery performance by containing an ester compound having a carbon-carbon unsaturated bond and a specific combined additive.
Claims
1. A non-aqueous electrolyte solution comprising a compound (A) represented by formula (I) and one or more compounds (B) selected from the group consisting of phosphates having a P-F bond and a P=O bond, sulfonates having an S-F bond, and borates having an oxalate group. 【Chemistry 1】 (In formula (I), R 1 ~R 6 are each independently a hydrogen atom or a hydrocarbon group; R 1 and R 2 , R 1 and R 3 , R 4 and R 5 , and R 5 and R 6 may be bonded to each other to form a cyclic structure, and n is an integer of 0 to 4.
2. In the formula (I), R 1 ~R 6 are each independently a hydrogen atom, an alkyl group having 1 to 6 carbon atoms, an alkenyl group having 2 to 6 carbon atoms, an aryl group having 6 to 12 carbon atoms, or an aralkyl group having 7 to 18 carbon atoms.
3. The nonaqueous electrolyte according to claim 1 or 2, wherein the compound (A) represented by the formula (I) is a vinyl ester compound represented by the following formula (II) and / or an allyl ester compound represented by the following formula (III). 【Chemistry 2】 (In formula (II), R 7 ~R 9 are each independently a hydrogen atom or a hydrocarbon group; R 7 and R 8 , R 7 and R 9 may be bonded to each other to form a cyclic structure. 【Chemistry 3】 (In formula (III), R 10 ~R 12 are each independently a hydrogen atom or a hydrocarbon group; R 10 and R 11 , R 10 and R 12 may be bonded to each other to form a cyclic structure.
4. The nonaqueous electrolyte solution according to any one of claims 1 to 3, wherein the compound (A) represented by the formula (I) is allyl methacrylate.
5. The nonaqueous electrolyte solution according to any one of claims 1 to 4, comprising 0.01 mass % or more and 10 mass % or less of the compound (A) represented by the formula (I).
6. The nonaqueous electrolyte solution according to any one of claims 1 to 5, comprising 0.01 mass % or more and 10 mass % or less of one or more compounds (B) selected from the group consisting of a phosphate having a P-F bond and a P=O bond, a sulfonate having an S-F bond, and a borate having an oxalate group.
7. A non-aqueous electrolyte secondary battery comprising: a positive electrode having a positive electrode active material capable of absorbing and releasing metal ions; a negative electrode having a negative electrode active material capable of absorbing and releasing metal ions; and the non-aqueous electrolyte according to any one of claims 1 to 6.
Citation Information
Patent Citations
Electrolyte of lithium ion secondary battery and the lithium ion secondary battery comprising same
CN104218257A
Lithium secondary battery
JP2000223154A
Nonaqueous electrolyte, and nonaqueous electrolyte battery
JP2007335170A
Nonaqueous electrolyte secondary battery
JP2009152133A
Nonaqueous electrolyte and nonaqueous electrolyte secondary battery using the same
JP2012043632A